The International Rankings System of Higher Education Institutions (methodological analysis) - Vardanyan, Armine (Journal of Sociology: Bulletin of Yerevan University, 2015)
The article presents the results of a comparative analysis of the most well-known international rankings methodologies in higher education institutions. It has identified the main criterions and directions for evaluation of higher education institutions activities. The identified directions, being taken as a basis for comparative analysis, provided the overall structure and logic of the sequential analysis for the each ranking system. It has presented the features appeared during the rankings based on the level of the criterions for evaluation of higher education institutions activities in the framework of certain rankings system.
Keywords: the higher education institutions rankings, the international higher education institutions rankings system, the ranking methodology, the criterions for evaluation of higher education institutions rankings activities, the higher education institutions directions activities